Effect of Packaging type on the Quality of Tomato Dodol During Storage - Eka putri, Angelly Risma; Faridah, Anni; Holinesti, Rahmi; Insan, Ranggi Rahimul (Universitas Negeri Padang, 2023)
This study discusses the effect of the type of packaging on the quality of Tomato Dodol during storage. The purpose of this study was to determine the effect of packaging on the quality of tomato lunkhead during storage using different types of packaging, namely plastic, corn husks, and wax paper. This type of research is pure experimental research using a completely randomized design (CRD) method and three repetitions. the data was analyzed using ANOVA, if Fcount > Ftable then the test will be continuedDuncan. The results of the study showed that the average was almost the same for each treatment and there was no significant effect on the use of the type of packaging, both in terms of shape, texture and color quality. There was no significant difference in the quality of the aroma on the first and fifth days for the three types of packaging, but on the eighth day the corn husk husks (X2) had an effect on the quality of the aroma, with an average value of 1 category without tomato flavor. and packaging with the best aroma was produced by plastic (X1) with an average of 3.13 in the tomato flavored category. then on the taste quality, the packaging did not affect the tomato dodol on the first and fifth days while on the eighth day the type of packaging that had an effect was corn husks with an average value of 0. on the eighth day of storage the tomato dodol packaged corn husks could no longer be consumed. From the overall average the best type of packaging that can maintain the quality of tomato lunkhead during storage is plastic packaging (X1)